2020
DOI: 10.1097/pgp.0000000000000737
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnostic Criteria for Chronic Endometritis: A Survey of Pathologists

Abstract: While acute endometritis is a reasonably well-defined entity of ascending infection and attendant active inflammation, chronic endometritis is less well defined. As part of a broad effort to define and refine the diagnostic criteria and management of the disease, we conducted a survey of pathologists to understand the variability in diagnostic criteria and implications of the diagnosis of nonspecific, nonobstetric chronic endometritis. Members of national and international professional pathology societies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…Chronic endometritis is a continuous in ammation of endometrium, there are lots of plasma cells in the endometrial stroma, as the marker, CD138 and CD38 are detected to nd plasma cells by immunohistochemistry(IHC) [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic endometritis is a continuous in ammation of endometrium, there are lots of plasma cells in the endometrial stroma, as the marker, CD138 and CD38 are detected to nd plasma cells by immunohistochemistry(IHC) [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Histological evidence of plasma cell in the endometrial tissue is reportedly the gold standard for diagnosis 3,4,13 21 and has been much debated amongst gynecologic pathologists since 14 22 making this criterion dated, nonspecific and left up to individual interpretation of the examining pathologist.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology textbooks broadly define the histologic diagnosis as “the presence of an unspecified number of endometrial stromal plasma cells”, 22 making this criterion dated, nonspecific and left up to individual interpretation of the examining pathologist. About a third (28.5%) of pathologists diagnose based on evidence of a single plasma cell 14 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasma cells present within the endometrium are often associated with reactive stroma, increased lymphocytic infiltrate, lymphoid aggregates and disordered glandular architecture; however, these changes are not required to render a diagnosis of chronic endometritis. 3 When present, chronic endometritis has been implicated in reduced reproductive potential, primarily through decreased embryo implantation and recurrent miscarriage. Several studies have suggested that treatment with antibiotics may improve subsequent reproductive outcomes in women with chronic endometritis, making screening and diagnosis essential to improving outcomes.…”
mentioning
confidence: 99%